1994
DOI: 10.1002/ajim.4700250117
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation fever and respiratory symptoms in the trimming department of swedish sawmills

Abstract: Mold dust exposure in the trimming departments of sawmills may cause inhalation fever as well as allergic alveolitis. Responses to questionnaires sent to 2,052 workers from trimming departments of 233 Swedish sawmills showed that one of five workers experienced work-related febrile attacks. A single case of allergic alveolitis was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…These findings are in line with other studies, which have found that HP-symptoms among wood trimmers are frequently reported, 5,13 but cases of severe HP are rare. 13 To our knowledge, this is the first study that included quantitative assessment of the suspected antigen/allergen during follow-up. An alternative hypothesis to explain the respiratory symptoms experienced by the employees would be that they had experienced organic toxic dust syndrome (ODTS) rather than acute episodes of HP.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are in line with other studies, which have found that HP-symptoms among wood trimmers are frequently reported, 5,13 but cases of severe HP are rare. 13 To our knowledge, this is the first study that included quantitative assessment of the suspected antigen/allergen during follow-up. An alternative hypothesis to explain the respiratory symptoms experienced by the employees would be that they had experienced organic toxic dust syndrome (ODTS) rather than acute episodes of HP.…”
Section: Discussionmentioning
confidence: 97%
“…The raw material is usually kept dry and is turned over relatively quickly, which decreases the risk of mold growth. Mold-contaminated raw material was not found during the visits at the plants, and nobody reported febrile attacks, which may appear at high exposure to molds—so-called inhalation fever (42,43). …”
Section: Discussionmentioning
confidence: 99%
“…In addition to sino-nasal cancer [IARC, 1995], exposure to dust of both hard (broad-leaved trees or Angiosperms) and softwood (conifers or Gymnosperms) has been shown to be associated with upper and lower respiratory symptoms, reduced lung function, increased bronchial responsiveness, occupational asthma, and eye and nose irritations [ChanYeung et al, 1984;Shamssain, 1992;Malo et al, 1994;Rask-Andersen et al, 1994;Hessel et al, 1995;Malmberg et al, 1996;Noertjojo et al, 1996;Demers et al, 1997]. The underlying pathophysiological mechanisms are unclear, and in case of Western red cedar asthma both allergic and nonallergic mechanisms have been suggested [Chan-Yeung, 1982, 1994Frew et al, 1998].…”
Section: Introductionmentioning
confidence: 99%